Lacunary A-statistical convergence and lacunary strong A-convergence sequences of order (?,?) with respect to a modulus - Sengul, Hacer; Et, Mikail; Cakalli, Huseyin (Amer Inst Physics, 2019)
In this paper, the definitions of lacunary strong A-convergence of order (alpha,beta) with respect to a modulus and lacunary A-statistical convergence of order (alpha,beta) are given. We study some connections between lacunary strong A-convergence of order (alpha,beta) with respect to a modulus and lacunary A-statistical convergence of order (alpha,beta).
3rd International Conference of Mathematical Sciences (ICMS) -- SEP 04-08, 2019 -- Maltepe Univ, Istanbul, TURKEY
Keywords: Sequences; series; summability; functional analysis